Rozwój Termosprężystości w Latach 1945-1960 - Ignaczak, J. (Engineering Transactions, 1960)
This is a brief survey of some theoretical investigations in thermo elasticity perfomed in the years 1945-1960 in more important scientific centres of the world. The survey is subdivided into the following sections: (1) The development of the science of thermoelasticity up to 1945. (2) The development of the science of thermoelasticity since 1945 up to the present. (2.1) The problem of thermal distortions as a basic problem for the solution of classical static and dynamic problems of thermoelasticity. (2.2) The new investigation trends in the last decade. The notion of thermoelastic solid -coupled problems of thermo-elasticity. Thermal stresses in viscoelastic structures. A brief description of some more important theoretical papers on thermoelastic problems indicates the high degree to which this domain of science developed after the Second World war.